Electrical, optical and photoconductive properties of Sn-doped indium sulfofluoride thin films. (January 2021) - Vygranenko, Y.; Fernandes, M.; Vieira, M.; Lavareda, G.; Nunes de Carvalho, C.; Brogueira, P.; Amaral, A.; Barradas, N.P.; Alves, E.
Abstract: This work reports on undoped and Sn-doped indium sulfofluoride thin-films deposited by radio-frequency plasma-enhanced reactive thermal evaporation. The deposition was performed evaporating pure indium or indium-tin alloy in SF6 plasma at substrate temperatures ranging from 373 to 423 K. Rutherford backscattering analysis and secondary-ion mass spectrometry were used to determine the chemical composition of the films. The film characterization includes electrical, optical, and photoconductivity measurements. The resistivity of undoped material varies in a wide range of 1 GΩ-cm to 2 TΩ-cm depending on deposition conditions. Sn doping leads to a decrease in the resistance down to 8 MΩ-cm. The films are highly transparent in the visible-infrared region due to an indirect bandgap of 2.7–3 eV. Moreover, the doped material is highly photosensitive in the blue - UV region. Photoconductivity kinetics under various excitation conditions was also studied. The synthesized material is a promising candidate for a buffer layer in chalcogenide-based solar cells.